2019
DOI: 10.1002/sctm.19-0234
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fibroblast growth factor 2 on the senescence of human adipose-derived mesenchymal stem cells during long-term culture

Abstract: Adipose‐derived mesenchymal stem cells (ASCs) exhibit great potential in regenerative medicine, and in vitro expansion is frequently necessary to obtain a sufficient number of ASCs for clinical use. Fibroblast growth factor 2 (FGF2) is a common supplement in the ASC culture medium to enhance cell proliferation. To achieve clinical applicability of ASC‐based products, prolonged culture of ASCs is sometimes required to obtain sufficient quantity of ASCs. However, the effect of FGF2 on ASCs during prolonged cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…Evidence indicates that FGF2 is implicated in diverse biological processes, including neurodevelopment, immune homeostasis, angiogenesis and neoplastic transformation [46]. Although the role of FGF2 in malignancies remains controversial, FGF2 has been proposed to act as a pro-oncogenic regulator during the development of OS [47][48][49]. In the present study, abnormally elevated levels of FGF2 mRNA and protein were consistently observed in OS tissues and cells.…”
Section: Discussionsupporting
confidence: 59%
“…Evidence indicates that FGF2 is implicated in diverse biological processes, including neurodevelopment, immune homeostasis, angiogenesis and neoplastic transformation [46]. Although the role of FGF2 in malignancies remains controversial, FGF2 has been proposed to act as a pro-oncogenic regulator during the development of OS [47][48][49]. In the present study, abnormally elevated levels of FGF2 mRNA and protein were consistently observed in OS tissues and cells.…”
Section: Discussionsupporting
confidence: 59%
“…Evidence indicates that FGF2 is implicated in diverse biological processes, including neurodevelopment, immune homeostasis, angiogenesis and neoplastic transformation [41]. Although the role of FGF2 in malignancies remains controversial, FGF2 has been proposed as a pro-oncogenic regulator during the development of OS [42][43][44]. In the present study, abnormally elevated levels of FGF2 mRNA and protein were consistently observed in OS tissues and cells.…”
Section: Discussionsupporting
confidence: 57%
“…However, a critical issue associated with the use of BM-MSCs is that, under adherent monolayer culture conditions, these cells eventually lose their stemness properties following repeated passages during culture expansion (Bonab et al, 2006;Stolzing et al, 2006;Wagner et al, 2008;Bork et al, 2010;Gu et al, 2016). It has been suggested that supplementing the culture medium with fibroblast growth factor (FGF)-2 (Tsutsumi et al, 2001;Cheng et al, 2020;Xu et al, 2020) and epidermal growth factor (EGF) (Tamama et al, 2006;Xu et al, 2020) can enable large-scale expansion of MSC cultures. However, these methods are limited as such supplements cannot sufficiently maintain the cellular differentiation potential in longterm culture (Gharibi and Hughes, 2012;Cheng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that supplementing the culture medium with fibroblast growth factor (FGF)-2 (Tsutsumi et al, 2001;Cheng et al, 2020;Xu et al, 2020) and epidermal growth factor (EGF) (Tamama et al, 2006;Xu et al, 2020) can enable large-scale expansion of MSC cultures. However, these methods are limited as such supplements cannot sufficiently maintain the cellular differentiation potential in longterm culture (Gharibi and Hughes, 2012;Cheng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%